Discourse on drone technology in Malaysia - Mimi Rabita, Abdul Wahit; Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
PEKAN, 15 August 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) held a knowledge discourse programme titled ‘Drone Technology in Malaysia: Are We Ready?’